Digital image in the hierarchy of cultural practices: a dialog about the ukrainian mediascape in times of war. Interview with Ruslan Bortnik - Павлова, Олена Юріївна (Київський національний університет імені Тараса Шевченка, 2023)
The topic of our conversation with political scientist, political technologist, director of the Ukrainian Institute of Politics Ruslan Bortnik is the media hierarchy in Ukraine and the modern world and the place of humanities and social sciences in information management.

Тема нашої розмови з політологом, політтехнологом, директором Українського інституту політики Русланом Бортником – ієрархія медіа в Україні та сучасному світі та місце гуманітарних і соціальних наук в управлінських відомостях.
Цифровий образ в ієрархії культурних практик: діалог про український медіашафт в умовах війни. Інтерв'ю з Русланом Бортніком
Keywords: медіашафт